2014
DOI: 10.5209/rev_hics.2013.v18.44260
|View full text |Cite
|
Sign up to set email alerts
|

Twitter y la polarización del debate político:análisis del caso #objetivodeguindos y #aznara3.

Abstract: Resumen:Este artículo estudiará cómo el debate social 2.0, es decir, aquel que se da en las redes sociales, más concretamente en Twitter, se polariza al tratar temas de índole política, social o ideológica. Por esto, un campo interesante de estudio son las entrevistas realizadas a José María Aznar en Antena 3 y a Luis de Guindos en la Sexta, ya que debido a la relevancia pública de ambos personajes, se propiciaron una serie de variables que permite analizar la polarización de las red social Twitter además la p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Marín‐Dueñas et al (2019) and Haman (2020) have identified strategies put in place by political actors (especially during electoral periods) to attract their potential voters in the networks that foster the polarization of the social debate in SM (Bustos & Capilla, 2014). Social rhetorical strategies with a high sentimental charge aim to give credibility to political interests and constantly confront the rest of the opponents.…”
Section: Literary Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Marín‐Dueñas et al (2019) and Haman (2020) have identified strategies put in place by political actors (especially during electoral periods) to attract their potential voters in the networks that foster the polarization of the social debate in SM (Bustos & Capilla, 2014). Social rhetorical strategies with a high sentimental charge aim to give credibility to political interests and constantly confront the rest of the opponents.…”
Section: Literary Overviewmentioning
confidence: 99%
“…But also the violation of tolerance, civility, and respect for specific groups or social collectives, such as migrants, the LGBT community, and certain religious groups (Matamoros-Fernández & Farkas, 2021). Marín-Dueñas et al (2019) and Haman (2020) have identified strategies put in place by political actors (especially during electoral periods) to attract their potential voters in the networks that foster the polarization of the social debate in SM (Bustos & Capilla, 2014). Social rhetorical strategies with a high sentimental charge aim to give credibility to political interests and constantly confront the rest of the opponents.…”
Section: Literary Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, some relevant media have identified the polarization of the political spectrum on Twitter or the existence of bots in Spain, using different data analysis methodologies to do so. Academic studies, however, are more inclined to research based on content analysis of user biographies (Bustos Díaz & Capilla del Fresno, 2013) or certain social issues such as gender (Orbegozo-Terradillos et al, 2020). Along the same lines, papers like the one by Blas et al (2019) have paid attention to the use of Twitter during key political moments such as election night, analyzing which groups lead the conversation on the network and highlighting the institutionalization of content production.…”
Section: The Use Of Twitter In Spanish Politics and Debatesmentioning
confidence: 99%
“…In this regard and as an example of the model, three issues are put forward in the literature. First, whether the effect of media polarisation is replicated or intensified in the social media in Spain as described in the traditional domain or off-line (Bustos & Capilla Del Fresno, 2014). Secondly, whether, on the basis of the characteristics described above, there is a selective exposure of audiences of a partisan nature (Humanes, 2014) also in social media, with the necessary intervention of digital communities in the orientation, definition and the framing of the news (López-López, Castro-Martínez & Oñate, 2020).…”
Section: The "Partisan Audience" In Social Networking Sites In Spainmentioning
confidence: 99%